Test of market structure and profitability in liberalizing the deposit market: The case of North Cyprus - Bektaş, Eralp (LLC CPC Business Perspectives, 2006)
This paper investigates profitability determinants of North Cyprus depository institutions using panel data between 1991 and 1997. It uses random-effect model to test market power (traditional SCP or collusion) and efficient-structure hypotheses for a single geographical deposit market The results obtained from the study show that none of these hypotheses holds for the North Cyprus deposit market during the study period. © Eralp Bektas, 2006.
Keywords: Banking; Market structure; North Cyprus; Profitability